The effects of environmental taxes and quotas on the optimal timing of emission reductions under Choquet-Brownian uncertainty - Elettra Agliardi; Luigi Sereno (Alma Mater Studiorum - Università di Bologna, Dipartimento di Scienze Economiche (DSE), 2011)
The effects of two environmental policy options for the reduction of pollution emissions, i.e. taxes and non-tradable quotas, are analyzed. In contrast to the prior literature this work endogenously takes into account the level of emissions before and after the adoption of the new environmental policy. The level of emissions is determined by solving the firm's profit maximization problem under taxes and fixed quotas. We find that the optimal adoption threshold under taxes is always larger than the adoption threshold under fixed quota, even in a setting characterized by ecological uncertainty and ambiguity - in the form of Choquet-Brownian motions - on future costs and benefits over adopting environmental policies.
Keywords: Q28; Q48; L51; H23; 330